Pengendalian Penyakit Layu Fusarium pada Pisang dengan Inokulasi Jamur Mikoriza Vesikular Arbuskular pada Bibit - Suryanti Suryanti; Arif Wibowo; Christanti Sumardiyono (Universitas Gadjah Mada, 2003)
Fusarium wilt disease caused by Fusarium oxysporum fsp. cubense is the most important and destructive disease on banana. The pathogen is soil-borne and can survive in soil without the occurence of the host. The Vesicular Arbuscular Mychorriza (VAM) is a symbiotic associated fungi and plant roots. The VAM which infected plant can induce the resistance to pathogen. Banana seedlings obtained from tissue culture one free from pathogen. The seedling was inoculated with VAM to induce the resistance to Fusarium wilt disease. The result showed that the seedling inoculated with VAM can reduce diseases intensity of Fusarium wilt on banana.